2020
DOI: 10.1002/adfm.202000511
|View full text |Cite
|
Sign up to set email alerts
|

Ag Nanoparticles Cluster with pH‐Triggered Reassembly in Targeting Antimicrobial Applications

Abstract: Antibacterial efficiency can be effectively improved by applying targeting antibacterial materials and strategies. Herein, the successful synthesis of uniform pH-responsive Ag nanoparticle clusters (AgNCs) is demonstrated, which can collapse and reassemble into nonuniform Ag NPs upon exposure to the acidic microenvironment of bacterial infections. This pH triggered reassembly contributes greatly to the improved antibacterial activities of AgNCs against both methicillin-resistant Staphylococcus aureus (MRSA) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
92
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 114 publications
(98 citation statements)
references
References 56 publications
1
92
0
Order By: Relevance
“…On the 9th day, immunofluorescence technology was introduced to illustrate the expression of vascular endothelial growth factor (VEGF) and cluster of differentiation 45 (CD45) to evaluate angiogenesis and inflammation of the wound. [ 41 ] As shown in Figure 4G, much lower expression of CD45 observes in the groups of Fe‐iCOF‐Gel and Glucose + GFeF‐Gel, indicating less inflammation. Meanwhile, the immunofluorescence intensity of VEGF is almost the same due to blood vessel formation.…”
Section: Resultsmentioning
confidence: 97%
“…On the 9th day, immunofluorescence technology was introduced to illustrate the expression of vascular endothelial growth factor (VEGF) and cluster of differentiation 45 (CD45) to evaluate angiogenesis and inflammation of the wound. [ 41 ] As shown in Figure 4G, much lower expression of CD45 observes in the groups of Fe‐iCOF‐Gel and Glucose + GFeF‐Gel, indicating less inflammation. Meanwhile, the immunofluorescence intensity of VEGF is almost the same due to blood vessel formation.…”
Section: Resultsmentioning
confidence: 97%
“…Experiments for in vivo wound healing demonstrated that pH-responsive silver nanoparticle clusters formed from the ortho ester inner layer and PEG corona (AgNCs) are effective for the healing of methicillin-resistant Staphylococcus aureus infections [77]. Transistors are usually utilized as electronic switches since they react pointedly with an amplified current output to an applied voltage threshold.…”
Section: Chemical-responsive Nanomaterialsmentioning
confidence: 99%
“…[124] Although SA-based hydrogel loaded with Ag NPs has good antibacterial ability, the loaded Ag NPs are unstable and released Ag ions exhibited obvious toxicity to normal cells and tissues. [125] Shin et al utilized formaldehyde as a reducing agent to prepare Ag NPs through the reduction reaction of Ag + that were electrostatically adsorbed onto the surface of TEMPO-oxidized cellulose nanofibers. [126] The immobilized Ag NPs were subsequently embedded in SA hydrogels.…”
Section: Natural Polymeric Matrixmentioning
confidence: 99%